2021
DOI: 10.7717/peerj.12325
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcode reference library construction and genetic diversity and structure analysis of Amomum villosum Lour. (Zingiberaceae) populations in Guangdong Province

Abstract: Background Amomum villosum Lour. is the plant that produces the famous traditional Chinese medicine Amomi Fructus. Frequent habitat destruction seriously threatens A. villosum germplasm resources. Genetic diversity is very important to the optimization of germplasm resources and population protection, but the range of inherited traits within A. villosum is unclear. In this study, we analyzed the genetic diversity and genetic structures of A. villosum populations in Guangdong and constructed a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…After obtaining convincing test results, the screening requirements were consistently based on the BSW values, ensuring a “100% identity” between the segments and the species. RNA barcoding technology provided the potential for batch identification by formulating particular barcode rules for various species ( Gong et al., 2021 ). Secondly, there is potential for further enhancement in the barcode analysis tools offered by the database, particularly in the area of generating dynamic barcodes with a single click.…”
Section: Discussionmentioning
confidence: 99%
“…After obtaining convincing test results, the screening requirements were consistently based on the BSW values, ensuring a “100% identity” between the segments and the species. RNA barcoding technology provided the potential for batch identification by formulating particular barcode rules for various species ( Gong et al., 2021 ). Secondly, there is potential for further enhancement in the barcode analysis tools offered by the database, particularly in the area of generating dynamic barcodes with a single click.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that the single plastome fragment is not suitable for the identification of several medicinal plants within the genus Amomum [55,61,63,[73][74][75][76]. The complete plastomes have demonstrated a strong capability to differentiate species of Amomum [55].…”
Section: Dna Barcoding In Six Medicinal Plants Within Amomummentioning
confidence: 99%
“…Gong et al. [ 44 ] built a reference library of Amomum villosum Lour. Populations for genetic diversity and structure analysis.…”
Section: Conventional Dna Barcodesmentioning
confidence: 99%